Resveratrol modulates phosphorylation of ERK and AKT in murine cementoblasts during in vitro orthodontic compression - Shams Negm; Michael Wolf; Rogerio B. Craveiro; Leon Schurgers; Joachim Jankowski; Rebekka K. Schneider; Marta Rizk; Franziska Coenen; Isabel Knaup; Sihem Brenji; Christian Niederau (BMC Oral Health)
Abstract Objective Resveratrol is a plant polyphenol known for its anti-inflammatory and pro-regenerative properties. These could be beneficial in controlling potential side effects of orthodontic treatment, such as apical root resorption. Orthodontic tooth movement occurs as part of a sterile inflammatory response. However, dysregulation of this process can result in pathologically increased osteoclast activity in the radicular vicinity, leading to unwanted root resorption. Previous studies have shown that root cementum cells can modulate recruitment of osteoclast precursors and cementum repair. Material and methods We investigated the effect of resveratrol on mechanically stimulated murine cementoblasts (OCCM-30) with regards to cell viability, and mRNA expression and protein levels of pro-inflammatory cytokines. Furthermore, the modulation of central related kinases was investigated. Results Resveratrol increased viability of OCCM-30 in a time- and dose-dependent manner and significantly reduced upregulation of pERK and pAKT, upstream regulators of key cellular metabolic pathways. Furthermore, we describe for the first time that cementoblasts respond to compression with accelerated activation of STAT3 and increased translocation of NF-κB p65 into the nucleus. Conclusion This study shows a regulation of pAKT and pERK by resveratrol in OCCM-30 cells without a negative effect on cell viability. Therefore, resveratrol may have the potential to modulate the periodontal response to mechanical stimulation.